2016
DOI: 10.7717/peerj.1994
|View full text |Cite
|
Sign up to set email alerts
|

Towards a barrier height benchmark set for biologically relevant systems

Abstract: We have collected computed barrier heights and reaction energies (and associated model structures) for five enzymes from studies published by Himo and co-workers. Using this data, obtained at the B3LYP/6- 311+G(2d,2p)[LANL2DZ]//B3LYP/6-31G(d,p) level of theory, we then benchmark PM6, PM7, PM7-TS, and DFTB3 and discuss the influence of system size, bulk solvation, and geometry re-optimization on the error. The mean absolute differences (MADs) observed for these five enzyme model systems are similar to those obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…In previous work, DFTB models have been tested using single point energies on structures determined by high‐level QM methods. In this work, we explicitly optimize TS structures with DFTB, using the ADF program package …”
Section: Resultsmentioning
confidence: 99%
“…In previous work, DFTB models have been tested using single point energies on structures determined by high‐level QM methods. In this work, we explicitly optimize TS structures with DFTB, using the ADF program package …”
Section: Resultsmentioning
confidence: 99%
“…The benchmark set of enzymatically catalyzed reactions consists of five chemical problems taken from the literature [73][74][75][76][77][78] but provided with reoptimized structures and accurate DLPNO-CCSD(T) [79] reference energies at the complete-basis-set (CBS) limit in 2019. [40,48] (Table 3).…”
Section: Enzymatically Catalyzed Reactionsmentioning
confidence: 99%
“…An estimate of the accuracy of barrier heights, Table 1, can be obtained from a survey [39] which reported that, for four enzymes that did not contain metal atoms, the mean absolute difference for barrier heights calculated using PM7 compared to the reference method B3LYP/6-311+G(2d,2p) [LANL2DZ]//B3LYP/6-31G(d,p) was 7 kcal mol -1 . An unfortunate consequence of the use of a restricted basis set in semiempirical methods is the reduction in the accuracy of prediction of transition state barrier heights.…”
Section: Discussionmentioning
confidence: 99%